Synthesis and crystal packing of perylene-derivatives with extreme sterically demanding pentaphenylbenzene bay-substituents. Issue 5 (5th January 2021) - Dusold, Carolin; Weiss, Corinna; Hampel, Frank; Hirsch, Andreas
Abstract : Extremely flexible PDI-PPBs: perylenes with a varying number of PPBs and different peri -moieties were synthesized. The isolated regioisomers exhibit remarkably different properties. X-ray crystallography reveals sufficient suppression of aggregation. Abstract : An unprecedented library of single and double bay-substituted perylene-pentaphenylbenzenes (PPBs) is presented. An extreme core-distortion as well as successful elimination of aggregation interactions of perylenes was confirmed by X-ray analysis. The isomerically pure perylene-PPB hybrids show remarkable differences in their photophysical properties with respect to their regiochemistry as well as different peri -functionalization.